2000
DOI: 10.1783/147118900101194652
|View full text |Cite
|
Sign up to set email alerts
|

Hysteroscopic management of intra-uterine devices with lost strings

Abstract: SummaryWe report a series of 38

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
7
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 3 publications
3
7
0
Order By: Relevance
“…The risk of uterine perforation is minimal when the procedure is performed under direct vision. 5 The present results demonstrate that Macaluso stent removal forceps with Versascope hysteroscopy for the removal of retained IUDs is a simple, safe, effective and acceptable technique. We recommend this procedure as a first-line option for the removal of a retained IUD in a secondary care setting.…”
Section: Discussionsupporting
confidence: 53%
See 2 more Smart Citations
“…The risk of uterine perforation is minimal when the procedure is performed under direct vision. 5 The present results demonstrate that Macaluso stent removal forceps with Versascope hysteroscopy for the removal of retained IUDs is a simple, safe, effective and acceptable technique. We recommend this procedure as a first-line option for the removal of a retained IUD in a secondary care setting.…”
Section: Discussionsupporting
confidence: 53%
“…We agree with Trivedi et al that blind manipulation with artery forceps, hooks and clamps for IUD retrieval may be potentially dangerous, producing cervical or uterine injuries. 5 Using a hysteroscope to locate and remove IUDs under general anaesthesia is a well-established technique. The risk of uterine perforation is minimal when the procedure is performed under direct vision.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies describing hysteroscopy‐guided removal of retained IUDs showed success rates from 88% to 100%, similar to what we found in our series. This approach is used once an IUD has failed to be extracted by the usual procedures; it usually requires hospitalization and anesthesia and is more expensive and less available in our health care system.…”
Section: Discussionsupporting
confidence: 90%
“…However, a study by Reiertsen confirmed that whilst reliable in detecting IUDs in utero, ultrasonography is not helpful in detecting cases of penetration into the uterine wall. 6 If routine retrieval methods fail, for the reasons alluded to previously, then most 'apparently lost' IUDs can be both located and then simply and safely removed using hysteroscopic aid. 7 Nevertheless some instances, as the present case illustrates, require more extensive surgery.…”
Section: Discussionmentioning
confidence: 99%